Sophie Laws, with Caroline Harper and Rachel Marcus. Research for Development: A Practical Guide. New Delhi: Vistaar Publications. 2003. xiii+475 pages. Paperback. Indian Rupees 450.00. (The Pakistan Development Review, 2003)
To implement any successful policy, research about the subject-matter is essential. Lack of knowledge would result in failure and, from an economic point of view, it would lead to a waste of scarce resources. The book under review is essentially a manual which highlights the use of research for development. The book is divided into two parts. Part One informs the reader about concepts and some theory, and Part Two deals with the issue of undertaking research for development. Both parts have 11 chapters each. Chapter 1 asks the basic question: Is research important in development work? The answer is that it is. Research has many dimensions: from the basic asking of questions to the more sophisticated broad-based analysis of policy issues. The chapter, in short, stresses the usefulness of research which development workers ignore at their own peril.